2019
DOI: 10.1002/glia.23699
|View full text |Cite
|
Sign up to set email alerts
|

Roles of glial ion transporters in brain diseases

Abstract: Glial ion transporters are important in regulation of ionic homeostasis, cell volume, and cellular signal transduction under physiological conditions of the central nervous system (CNS). In response to acute or chronic brain injuries, these ion transporters can be activated and differentially regulate glial functions, which has subsequent impact on brain injury or tissue repair and functional recovery. In this review, we summarized the current knowledge about major glial ion transporters, including Na+/H+ exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 248 publications
1
57
0
Order By: Relevance
“…Apart from recommending follow-up research into the therapeutic potential of cell-free miR-146a-5p in the context of I/R injury and inflammatory disorders, results raise a number of interesting theoretical questions. For example, it is unknown whether hUMSC-Exosomal cargo is also perhaps involved in regulating glial ion transporters (which are involved in the Warburg effect, glial activation, neuroinflammation, and neuronal damage during glioma [ 63 ]). Additionally, might other miRNAs impact microglial function after ischemic stroke?…”
Section: Discussionmentioning
confidence: 99%
“…Apart from recommending follow-up research into the therapeutic potential of cell-free miR-146a-5p in the context of I/R injury and inflammatory disorders, results raise a number of interesting theoretical questions. For example, it is unknown whether hUMSC-Exosomal cargo is also perhaps involved in regulating glial ion transporters (which are involved in the Warburg effect, glial activation, neuroinflammation, and neuronal damage during glioma [ 63 ]). Additionally, might other miRNAs impact microglial function after ischemic stroke?…”
Section: Discussionmentioning
confidence: 99%
“…However, under specific conditions such as cerebral ischemia, the expression of NKCCs can be altered [ 94 ]. Overstimulation of NKCC1 and other major glial ion transporters (such as Na + /H + , Na + /Ca 2+ and Na + /HCO 3 − exchangers) can contribute to glial apoptosis, inflammation, demyelination, inflammation, and excitotoxicity [ 26 ]. This cascade of events is involved in the development and progression of neurological diseases such as stroke [ 26 ].…”
Section: Role Of Nnkcc1 In Strokementioning
confidence: 99%
“…Overstimulation of NKCC1 and other major glial ion transporters (such as Na + /H + , Na + /Ca 2+ and Na + /HCO 3 − exchangers) can contribute to glial apoptosis, inflammation, demyelination, inflammation, and excitotoxicity [ 26 ]. This cascade of events is involved in the development and progression of neurological diseases such as stroke [ 26 ]. Studies have demonstrated evidence of increase NKCC1 expression in neurons, a phenotype resembling immature neurons, following an ischemic stroke [ 95 , 96 , 97 ].…”
Section: Role Of Nnkcc1 In Strokementioning
confidence: 99%
See 1 more Smart Citation
“…GABA is the primary neurotransmitter in the SCN [135]; it is the only neurotransmitter that is produced and received by SCN neurons [136]. Furthermore, both GABA A and GABA B receptors are present in more than 90% of SCN neurons [131,135,137,138]. GABA A R activity controls the ability of the pacemaker to shift state in response to light [131,135,139].…”
Section: Kcc2 and Gaba Involvementmentioning
confidence: 99%